Comparison of Stern Wedge and Stern Flap on Fast Monohull Vessel Resistance - Jadmiko, Edi; Arief, Irfan Syarif; Arif, Lukman (International Journal of Marine Engineering Innovation and Research, 2025)
Ship resistance is main factors that can give more effect the design of a ship. In studies do it with a design modification of the stern form. The addition of stern design to establish Stern flaps and Stern wedge that will be affect the value of resistance and flow patterns sistem that follow in the stern so that the resistance will be smaller. In this final project will be reseach about resistance on the stern at Barehull shape, and with the addition of Stern flaps or Stern wedge with variations of chord length and chord angle. The focus of this reseach is reduction in ship resistance generated when the ship operates with stern flaps or stern wedges. The simulation is done by Computational Fluid Dynamics (CFD) method using NUMECA Fine Marine software. The results of the analysis can be seen in the addition of the stern and flow patterns sistem that follow. Based on the result of simulation, the most optimal stern form performance reduces the resistance is Stern flap 1% Lpp with angle 4°. The resistance value is reduced to 9.33 kN or 3.5% at 28 knots.